Stock profesional, eficiencia educativa y segmentación: análisis de los procesos de formación profesional en Chile1 (2015)
This article describes and compares the relative position of the various professional careers in a set of education indexes expressive of traming processes and attributes of the group of graduates. It is a relevant event in a scenario of higher education as the chilean, characterized by high rates of coverage and the presence of a diversified range of segmented quality. These indexes report a high rate of graduates who do foresee problems of employability and depreciation of educational credentials; differential levels of retention and educational efficiency and structural process of elitization of the professional choice. This behavior is a manifestation of a pre-existing socio-educational segmentation process that extends and deepens the university space.